2008
DOI: 10.3928/01913913-20081101-02
|View full text |Cite
|
Sign up to set email alerts
|

Structural Sequelae and Refractive Outcome After Successful Laser Treatment for Threshold Retinopathy of Prematurity

Abstract: The study revealed various structural sequelae and their correlation with refractive outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
2
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 31 publications
4
36
2
5
Order By: Relevance
“…9,10,17 Our study and other case series found a lower SE in patients treated with IVB than in patients treated with cryotherapy (range, À 6.5 to À 3.51 D) or with laser peripheral ablative therapy (range, À 4.71 to À 1.50 D). [3][4][5][6][7] Our prevalences of myopia and high myopia are also similar to those of preschool-age patients in a recent case series who were treated with IVB only (55.6% and 11.1 to 17.0%) ( Table 3). 9,10,17 In the current study, the prevalences of myopia and high myopia increased significantly with the severity of ROP but were not associated with AXL changes.…”
Section: Eyesupporting
confidence: 59%
See 2 more Smart Citations
“…9,10,17 Our study and other case series found a lower SE in patients treated with IVB than in patients treated with cryotherapy (range, À 6.5 to À 3.51 D) or with laser peripheral ablative therapy (range, À 4.71 to À 1.50 D). [3][4][5][6][7] Our prevalences of myopia and high myopia are also similar to those of preschool-age patients in a recent case series who were treated with IVB only (55.6% and 11.1 to 17.0%) ( Table 3). 9,10,17 In the current study, the prevalences of myopia and high myopia increased significantly with the severity of ROP but were not associated with AXL changes.…”
Section: Eyesupporting
confidence: 59%
“…The reported rates range from 55.2 to 80.4% and 23.9 to 31.5%, respectively (Table 3). 3,4,6 The reported rates of myopia and high myopia were even higher in patients treated with cryotherapy, ranging from 82.9 to 92.0% and 32.0 to 52.5%, respectively (Table 3). [5][6][7] In the current study, the percentages of patients with myopia and high myopia among IVB-treated patients were 47.5 and 10.0%, respectively, which are less than the previously reported percentages for patients treated with laser treatment or cryotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Laser treatment has been well-described as a cause of advanced refractive errors in severe cases of ROP (27,28) . Conversely, studies have reported IVB treatment leads to lower degrees of myopic refraction than laser ablation.…”
Section: Discussionmentioning
confidence: 99%
“…Anisometropia and strabismus are the predominant risk factors for the development of amblyopia in children following laser ablation for severe ROP (28)(29)(30) . The present study demonstrated significantly higher rates of refractive anisometropia and strabismus following laser treatment compared to IVB monotherapy.…”
Section: Discussionmentioning
confidence: 99%